Garden of Saihoji temple built during the Muromachi period - Uralov Axtam Sindarovich; Boboeva Fotima Sobirjonovna (Genius Journals, 2023)
The article analyzes the development of traditional Japanese garden art during the Muromachi period using the example of one of the best Japanese traditional gardens - Saihoji Temple. The influence of Zen Buddhism on the nature, character and composition of the Saihoji Temple Garden is analyzed
Keywords: Muramachi; Musa Soseki; mosses